APPENDICULAR CARCINOID IN A VICTIM WITH SIMULTANEOUS CHEST AND ABDOMEN TRAUMA - E. V. Tatarinova; G. A. Nefedova (Неотложная медицинская помощь, 2017)
The article reports a clinical case of surgical therapy of a patient with simultaneous chest and abdomen trauma and carcinoid of the appendix.